Manpower Constraints and Corporate Policies - Francesco D'Acunto; Michael Weber; Shuyao Yang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Manpower constraints are the pervasive lack of specialized high- and low-skill workers, irrespective of the wage firms might offer. For a panel of German firms, we show manpower-constrained firms have higher capacity utilization and longer backlog of orders (measured in months). They are more willing to increase their capital expenditures, and more willing to grow their employment in the following year. Manpower constraints vary substantially over time and across industries, being higher on average in traditional manufacturing industries and lower in high-tech industries. For identification, we exploit the fall of the Berlin Wall in 1989, and the subsequent differential fluxes of Eastern immigrants across Western states, which followed the pre-existing patterns of Eastern German immigration immediately after WWII. We construct a Manpower Constraint (MPC) Index calibrating the loadings on firm-level financials that are also available in commonly used data set for US, European, and Asian firms. Our results help inform relevant debates such as the reform of immigration policies and the investment in public and private education for low-skilled workers.
Keywords: J21; J31; J61; G31; G32; 330; investment; skilled workers; immigration policies; education policies; economic growth